Neural stem cells and oligodendrocyte progenitor cells compete for remyelination in the corpus callosum - Moyon, Sarah; Holloman, Mara; Salzer, James L. (Frontiers in Cellular Neuroscience, 2023)
A major therapeutic goal in demyelinating diseases, such as Multiple Sclerosis, is to improve remyelination, thereby restoring effective axon conduction and preventing neurodegeneration. In the adult central nervous system (CNS), parenchymal oligodendrocyte progenitor cells (pOPCs) and, to a lesser extent, pre-existing oligodendrocytes (OLs) and neural stem cells (NSCs) from the sub-ventricular zone (SVZ) are capable of forming new myelin sheaths. Due to their self-renewal capabilities and ability to migrate widely within the CNS, NSCs represent an additional pool of remyelinating cells that may be targeted to supplement repair by pOPCs. However, in demyelinating disorders and disease models, NSC contribution to myelin repair is modest and most evident in regions close to the SVZ. We hypothesized that NSCs and pOPCs may compete to remyelinate the same axons, with pOPCs serving as the primary remyelinating cells due to their widespread distribution within the adult CNS, thereby limiting the contribution of NSCs. Here, we have used a dual reporter, genetic fate mapping strategy, to characterize pOPCs and NSCs contribution to remyelination after cuprizone-induced demyelination. We have confirmed that, while pOPCs are the main remyelinating cells in the corpus callosum, NSCs are also activated and recruited to demyelinating lesions. Blocking pOPC differentiation genetically, resulted in a significant increase of NSC recruitment into the demyelinated corpus callosum and their differentiation into OLs. These results strongly suggest that pOPCs and NSCs compete to repair white matter lesions. They underscore the potential significance of targeting NSCs to improve repair when the contribution of pOPCs is insufficient to effect full remyelination.